Counselling Skills and Studies - Ballantine Dykes, Fiona; Postings, Traci; Kopp, Barry; Counselling and Psychotherapy Central Awarding Body (Los Angeles : SAGE, 2017)
This practical guide will provide readers with the ideal 'way-in' to counselling, whether they are looking to use counselling skills to enhance their existing helping role or are taking their first steps towards becoming a professional counsellor.
Previous edition: 2014.
At foot of cover title: CPCAB.
Includes bibliographical references and index.
Keywords: Counseling; Society